Where is it? Examining Post-Secondary Students' Accessibility to Policies and Resources on Sexual Violence - Magnussen, Jacey; Shankar, Irene (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2019)
Faced with a growing demand for adequate policies and programs that meaningfully address sexual violence on campus, the provinces of British Columbia, Ontario and Manitoba have introduced legislation requiring all post-secondary institutions to institute a sexual assault policy. The remaining provinces and territories do not have similar legislation. In absence of such legislation, using the case study of Alberta, we examined how equipped post-secondary institutions in this province are to assist students in need. Utilizing publicly available data we examined: 1) whether Alberta’s post-secondary institutions have a sexual violence policy which is readily and easily accessible to the student; and 2) the ease with which students can access university resources and support services for sexual violence. The results indicate that most institutions do not have an accessible policy and support services for students in need. We are hopeful that this study can inform those designing and advocating for sexual violence policies on campus to institute measures to clarify institutions’ sexual violence policies, increase accessibility to those policies, create policies where they are missing, and work on clarifying the availability of resources for students on and off campus.